Digitalization and Evolution of Online Marketing on the Business Market in Romania - Raluca-Giorgiana (POPA) CHIVU; Otilia-Elena PLATON; David-Florin CIOCODEICĂ; Ionuț-Claudiu POPA (Communications of International Proceedings, 2021)
Online marketing and digital commerce are topics increasingly debated in the literature, highlighting their efficiency and usefulness in many cases. It has been proven that online marketing is effective due to the high degree of Internet users. In contrast, online commerce has proven effective due to the advantages of time to purchase, the ability to compare products, etc. However, the basis of all online aspects still consists of Internet use, which is why this article aims to analyze (using official statistics) the degree of Internet use on the Romanian market and the evolution of the number of companies using marketing online and e-commerce.
Keywords: Digitalization; Online Marketing; Business Market In Romania.